Про точні умови глобальної стійкості різницевого рівняння, яке задовольняє умову Йорка - Неня, О.І.; Ткаченко, В.І.; Трофімчук, С.І. (Український математичний журнал, 2008)
В продолжение предыдущих исследований авторов приведены простые достаточные условия глобальной устойчивости нулевого решения разностного уравнения xn+1 = qxn + fn (xn ,..., xn-k ), n ∈ Z, где нелинейные функции fn удовлетворяют условию Йорка. Для каждого натурального k интервал (0, 1] представлен как объединение [(2k + 2)/3] подынтервалов, и для q с каждого подынтервала в явном виде приведено условие глобальной устойчивости. Полученные условия являются точными для класса уравнений, удовлетворяющих условию Йорка. Continuing our previous investigations, we give simple sufficient conditions for the global stability of the zero solution of the difference equation x n+1 = qx n + ƒn(x n, …, x n−k), n ∈ ℤ, where the nonlinear functions ƒn satisfy the Yorke condition. For every positive integer k, we represent the interval (0, 1] as the union of [(2k + 2)/3] disjoint subintervals, and, for q from each subinterval, we present a global-stability condition in explicit form. The conditions obtained are sharp for the class of equations satisfying the Yorke condition.